2021
DOI: 10.1111/dth.14820
|View full text |Cite
|
Sign up to set email alerts
|

Different hair loss patterns in two pediatric patients with COVID‐19‐associated multisystem inflammatory syndrome in children

Abstract: Interpretation of the data; critical review of the literature; critical review of the manuscript. Akın Aktaş: Interpretation of the data; critical review of the literature; critical review of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Table 2 delineates the demographics and clinical characteristics of patients with hair loss and COVID‐19 ( n = 58), with a predominance of female patients (17.2% male and 82.8% female). 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 Hair loss type was predominately TE (74.1%), with the next most common hair loss type being early‐onset effluvium (12.1%). Only a small number of individuals had other types of hair loss including AA (5.2%), fibrosing alopecia (3.4%), and one individual each with alopecia areata totalis (1.7%), alopecia areata universalis (1.7%), and anagen effluvium (1.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 delineates the demographics and clinical characteristics of patients with hair loss and COVID‐19 ( n = 58), with a predominance of female patients (17.2% male and 82.8% female). 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 Hair loss type was predominately TE (74.1%), with the next most common hair loss type being early‐onset effluvium (12.1%). Only a small number of individuals had other types of hair loss including AA (5.2%), fibrosing alopecia (3.4%), and one individual each with alopecia areata totalis (1.7%), alopecia areata universalis (1.7%), and anagen effluvium (1.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Hair loss following the infection by SARS‐CoV‐2 did not spare the pediatric population: As a matter of fact, Hayran at al 17 . described two patients who were 10 and 13 years of age who developed TE and alopecia areata, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hair loss following the infection by SARS-CoV-2 did not spare the pediatric population: As a matter of fact, Hayran at al. 17 A recently published multicentric Spanish study identified 191 cases of post-infectious TE related to COVID-19: 78.5% of the patients were female, and 21.4% were male 20 . The mean age of the cohort was 47,4 years (range 15-88), and the days between coronavirus detection and beginning of hair loss were 57,1 (SD 18,3) on average 20 .…”
Section: Re Sultsmentioning
confidence: 99%
“…Individual patient characteristics for reports of new-onset alopecia areata following SARS-CoV-2 infection are outlined in Table I. [6][7][8][9][10][11] The average age of the patients was 37 years (range, 13-56 years). Four patients (57%) were female, and 3 patients (43%) were male.…”
Section: Resultsmentioning
confidence: 99%